JALALUDDIN RUMI’S MASNAVI AND HIS ETHICAL IDEAS (Neo Scientific Peer Reviewed Journal, 2025)
This article explores the ethical concepts presented in Jalaluddin Rumi’s renowned work Masnavi. Rumi, as a leading figure in Islamic mysticism and Sufi philosophy, conveys profound moral and spiritual teachings through allegories, parables, and poetic narratives. The paper examines Rumi’s approach to ethics, including themes such as self-awareness, love, compassion, humility, and the journey toward inner purification. It also highlights how these ethical teachings are relevant in both traditional and contemporary contexts, offering guidance for personal development and harmonious human relationships.